Evaluasi Pemberian Makanan Tambahan (PMT) dan Riwayat Sakit pada Anak Balita Stunting di Wilayah Kerja Puskesmas Salbait Kecamatan Mollo Barat - Murtin A. M. Anone; Jutomo, Lewi; Anna H. Talahatu (Yayasan Literasi Sains Indonesia, 2025)
Stunting is a condition of failure to grow in children due to malnutrition chronicle in the first 1000 days of Life (HPK) which is marked with TB/U has a z-score limit of less than -2 SD. Government efforts to handle the problem of stunting in toddlers is by providing additional food in the form of complete ready-to-eat meals or snacks made from local food ingredients. Objective of this research is to start giving additional food (PMT) and history of illness in stunting children under five at the Work Area Health Center Salbait, West Mollo District. This type of research is quasi experiment with a pre-posttest without control design. Deep sample this study consisted of 60 people. Sampling technique in this research namely simple random sampling. The data analysis used the insdependent sample t-test statistical test. Based on the research results, it shows that providing food Supplement (PMT) (P = < 0.001) can increase energy and protein intake (P = < 0.001), as well as weight body and height (P = <0.001), and reduce the duration of illness (P = < 0.001). In conclusion: there is an influence of supplementary feeding (PMT), and history of illness on the incidence of stunting in children under five in the Work Area Salbait Health Center, West Mollo District.